2006
DOI: 10.1196/annals.1371.013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Exposure to PAHs in Asphalt Workers by Environmental and Biological Monitoring

Abstract: In the present article we assessed exposure to polycyclic aromatic hydrocarbons (PAHs) in Italian asphalt workers (AW, n = 100), exposed to bitumen fumes and diesel exhausts, and in roadside construction workers (CW, n = 47), exposed to diesel exhausts, by means of environmental and biological monitoring. 1-hydroxypyrene (OH-Py) was determined in urine spot samples collected, respectively, after 2 days of vacation (baseline), before, and at the end of the monitored work shift, in the second part of the workwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 26 publications
(40 reference statements)
4
27
2
Order By: Relevance
“…Results of urinary OH-Py, already reported in a previous article, (21) values of OH-Py in baseline, before-and end-shift samples were 228, 402, and 690 ng/L for AW (p < 0.01) and 260, 304, and 378 ng/L for CW. Before-and end-shift levels were higher in AW than in CW (p < 0.05).…”
Section: Oh-py In Urinementioning
confidence: 72%
See 3 more Smart Citations
“…Results of urinary OH-Py, already reported in a previous article, (21) values of OH-Py in baseline, before-and end-shift samples were 228, 402, and 690 ng/L for AW (p < 0.01) and 260, 304, and 378 ng/L for CW. Before-and end-shift levels were higher in AW than in CW (p < 0.05).…”
Section: Oh-py In Urinementioning
confidence: 72%
“…(20,21) The partitioning of PAHs was such that 99% was detected in the vapor phase (low-boiling compounds) and 1% in the particulate phase (high-boiling compounds). A-NAP was the most abundant compound (median value 426 and 371 ng/m 3 , contributing for 82% and 94% to the total amount, in AW and CW, respectively), followed by A-PHE (52 and 14 ng/m 3 , 7% and 2%, p < 0.01), A-FLE (34 and 9 ng/m 3 , 5% and 2 %, p < 0.01), A-PYR (26 and 1 ng/m 3 , 3% and <1 %, p < 0.01), A-ACE (9 and 2 ng/m 3 , 1% and <1 %, p < 0.01), A-FLT (2.8 and 1.3 ng/m 3 , <1% in both cases, p < 0.01), and A-ANT (0.7 and 0.4 ng/m 3 , <1% in both cases, p < 0.01).…”
Section: Personal Exposure To Airborne Pahsmentioning
confidence: 99%
See 2 more Smart Citations
“…The major route of occupational exposure to asphalt is by inhalation, but its components may also be absorbed through the skin (Wolff et al, 1989). Epidemiological investigations have established mounting evidence that chemicals found in asphalt fumes present carcinogenic and possibly immunotoxic hazards (Campo et al, 2006). Exposure to asphalt fumes has been suggested as a cause of lung cancer, and other studies have reported cancers of the digestive tract, stomach (Maizlish et al, 1988;Hansen, 1989Hansen, , 1991Engholm et al, 1991;Partanen and Boofetta, 1994) and the urinary system (Bender et al, 1989;Hansen, 1989) such as bronchitis, emphysema and asthma identified in asphalt workers suggests that asphalt fumes contain immunotoxic compounds (Maizlish et al, 1988;Hansen, 1991;Norseth et al, 1991;Gamble et al, 1999).…”
Section: Introductionmentioning
confidence: 99%